2015
DOI: 10.1073/pnas.1500245112
|View full text |Cite
|
Sign up to set email alerts
|

Base-enhanced catalytic water oxidation by a carboxylate–bipyridine Ru(II) complex

Abstract: In aqueous solution above pH 2.4 with 4% (vol/vol) CH 3 CN, the complex [Ru II (bda)(isoq) 2 ] (bda is 2,2′-bipyridine-6,6′-dicarboxylate; isoq is isoquinoline) exists as the open-arm chelate, [Ru II (CO 2 -bpy-CO 2 − )(isoq) 2 (NCCH 3 )], as shown by 1 H and 13 C-NMR, X-ray crystallography, and pH titrations. Rates of water oxidation with the open-arm chelate are remarkably enhanced by added proton acceptor bases, as measured by cyclic voltammetry (CV). In 1.0 M PO 4 3-, the calculated half-time for water oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
168
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 134 publications
(204 citation statements)
references
References 36 publications
16
168
3
Order By: Relevance
“…[7] This behavior is also known for other catalysts and originates from the involvement of proton transfer in the rate-limiting step. [8] However, the [Ru(bda)(L) 2 ] family of catalysts follows a bimolecular pathway for OÀO bond formation.…”
mentioning
confidence: 71%
“…[7] This behavior is also known for other catalysts and originates from the involvement of proton transfer in the rate-limiting step. [8] However, the [Ru(bda)(L) 2 ] family of catalysts follows a bimolecular pathway for OÀO bond formation.…”
mentioning
confidence: 71%
“…Under these conditions, MeCN is coordinated to the Ru(II) form of the catalyst, Scheme 4, with pK a = 2.4 for the open-arm −COOH chelate. 11 The first quasi-reversible wave at E 1/2 = 0.62 V vs the saturated calomel electrode (SCE; 0.24 V vs NHE) arises from a 2e − /2H + Ru IV/II couple at this pH. 16 Oxidation of the Ru(II) form of the complex is accompanied by exchange of …”
Section: Methodsmentioning
confidence: 99%
“…It also highlights the role of electron transfer mediation at the oxide. 11 The larger overpotential for water oxidation at ITO−RuP 2+ in Figure 8 is due to the higher potential of the relay couple with E o = 1.07 V for ITO−RuP 3+/2+ compared to E o = 0.78 V for the Ru V/IV (O) +/0 couple.…”
Section: Acs Catalysismentioning
confidence: 96%
“…44−46 In a recent mechanistic study on water oxidation by an analogous Ru II (bda) catalyst, water oxidation was shown to occur following oxidation to Ru V (O) + and rate-limiting O atom transfer to water. 31 In the surface-bound assembly under steady-state photolysis conditions, assuming the same ratelimiting step, the assembly would exist as FTO|nanoSnO 2 | TiO 2 (3 nm)|-Ru III -Ru V (O) + , eq 1. Under these conditions, chromophore decomposition as −Ru III presumably competes with rate-limiting water oxidation, explaining the loss in O 2 evolution while maintaining decreased but sustained photocurrents.…”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 99%